PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS LUMI EDUCATION TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS VIII SMP NEGERI 2 CIBEUREUM - Ahmad Siddiq Apriasandy; Ipan Ripai (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low engagement of students in the learning process and the suboptimal learning outcomes resulting from the use of conventional instructional media in Indonesian language subject at SMP Negeri 2 Cibeureum. This research aims to examine the implementation of Lumi Education-based interactive learning media, to assess student learning outcomes before and after its implementation, and to evaluate the effectiveness of this media on the Indonesian language learning outcomes of eighth-grade students. The study employed a quantitative approach with a quasi-experimental method using a Pretest-Posttest Control Group Design, involving 25 students in the experimental class and 24 students in the control class. Data were analyzed using normality tests, homogeneity tests, independent sample t-test, paired sample t-test, and N-Gain analysis. The results show that the average score of the experimental class increased from 49.20 (pretest) to 78.80 (posttest), while the control class increased from 46.25 to 76.04. The N-Gain of the experimental class (0.6034) was descriptively higher than the control class (0.5588), yet the independent sample t-test on the posttest (sig. 0.382) and on the N-Gain (sig. 0.317) did not show a statistically significant difference between the two groups.